Analysis of Price, Promotion, and Brand Awareness on the Consumptive Behavior of Teater Adab Student Activity Unit Members on Shopee - Chahyanti, Avid Millatur Eka; Cindia, Ike; Putri, Atina Rokhmani (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study analyzes the influence of price, promotion, and brand awareness on the consumptive behavior of members of the Teater Adab Student Activity Unit at Universitas Nusantara PGRI Kediri on the Shopee platform. The purpose of this research is to explore the partial and simultaneous effects of these variables. This study employs a quantitative approach with a causal research design. The sampling technique used is saturated sampling, involving 88 student respondents who are members of the Teater Adab organization. Data were collected through an online questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 23. The results indicate that the independent variables—price, promotion, and brand awareness—have a positive and significant influence on students’ consumptive behavior, both partially and simultaneously. Among the three, promotion demonstrates the most dominant effect on consumptive behavior. The coefficient of determination (Adjusted R²) of 0.983 shows that 98.3% of the variation in consumptive behavior can be explained by these variables. The novelty of this study lies in its focus on students involved in a campus student activity unit, who exhibit unique consumptive characteristics yet are rarely examined within the context of e-commerce. These findings are expected to contribute to the development of more effective and relevant digital marketing strategies targeted at students. Overall, this research emphasizes the importance of integrated marketing strategies that consider competitive pricing, creative promotional activities, and strong brand identity to attract young consumers in the digital era, particularly among members of the Teater Adab student organization